On The Form and Judgment Function of Sense of Language - Duan Wenhua (Bina Nusantara University, 2014)
In parole communication, people are always able to judge whether others’ expressions are proper or not, understandableor not, elegant or not. In the field of teaching Chinese as a foreign language, teachers can also quickly point out the problems in students’ expressions and writing. This kind of direct sense is called Sense of Language. Generally speaking, Sense of Language is considered as a kind of “ability of subjective judgment”. In fact, there is a guide behind Sense of Language, which is profound rational theory proved by Psychology and Cerebral Science. Sense of Language will be discussed carefully in this article.